Fungsi, Pendekatan, dan Bidang Garapan Pengelolaan Pendidikan Islam - Moh. Chairurrozikin; Haris Subahtiar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
In Islam, every action must be carried out carefully, correctly, orderly, and regularly, avoiding indiscriminate actions. The management of education in Islam must be done with precision and seriousness. Islamic education management is considered crucial in improving the quality of life of people who are experiencing underdevelopment, including moral, material, and spiritual aspects. This research method uses Library Research. In the context of